Ibn al - Anbariâs Method In Explaining the Muallaqatâs Terms - Somayeh Hasan Alian; Sayyedmohammadreza Ibnorrasool (دراسات في اللغة العربيّة وآدابها)
As Muallaqat is of considerable significance in Arabic literature, syntactic studies, interpretation, and other language-related sciences, and because they include words from pagan (Jahlieh) period, many of commentators have paid much attention to them. The present study intended to examine the method of Ibn al Anbari in explaining Muallaqatâs Vocabulary. It employs a descriptive-analytical method. The most important findings are that Ibn al Anbari paid especial attention to lexicon and the term Muallaqat and spared no effort to explain phonological and syntactic points. Therefore, His commentaries include the meanings and synonyms many strange and difficult words and deals with syntactic issues related to them. His frequent reference to various pieces of evidence in explaining and defining the words displays his mastery of syntax and vocabulary.